Spatial Perception: How Paper Art Realizes the Expansion Design of Urban Spaces - Dingwei Zhang; Xiaotong Zhang; Hongtao Zhou (Buildings, 2025)
Aiming at the problems of insufficient function, cultural aphasia, and blunted perception faced by contemporary urban public space, this study explores the potential of paper-based materials in enhancing spatial quality and realizing spatial expansion effects, providing new solutions for urban renewal. Taking the sensory plasticity, visual aesthetics, cultural carrying, and ecological and environmental protection of paper materials as the entry point, we constructed a theoretical model of “paper art space expansion”. Through the design intervention strategy, we explored the application of paper art in the design of interface, space, art creation, and cultural empowerment from visual and tactile perspectives. Through course design, artist interviews, and questionnaire analysis, the study shows that (1) paper material can achieve a balance between function and aesthetics through multi-dimensional design strategies; (2) its environmental attributes and emotional healing value can effectively enhance the emotional connection between people and space; and (3) the contemporary translation of paper art provides an important path for cultural empowerment. This study forms a three-dimensional design framework of “Perception Layer-Technology Layer-Cultural Layer” and proposes a set of innovative models for the application of paper materials in contemporary art and space design, which can provide support for the expansion of space and the increase in content. Future research will focus on the transition of paper art from decoration to the design paradigm of the cultural narrative of intelligent space, deepening the value of paper material as an ecological, cultural, and technological medium, and open up a new direction for the theory and practice of spatial design. At the same time, more attention will be paid to the exploration of the possibility of sensory healing for the blind and other special populations.